Analysis of Physical Fitness and Health Status of the Teacher Professional Edaucation Program (PPG) Universitas Negeri Jakarta - Sujarwo; Oman Unju Subandi; Mustafa Masyhur (Indonesian Journal of Sport Management, 2025)
Background: Physical fitness and health are crucial factors contributing to teacher effectiveness. In fact, the intensity of academic activities and high course load often contribute to a decline in the physical fitness of PPG participants. Purpose: Conducting an analysis of the level of physical fitness and health status of participants in the teacher professional education program (PPG) Universitas Negeri Jakarta. Methods: The research method used is a qualitative method where the author collect data, for physical fitness used bleep test and for nutritional used interview from key subjects. The population was all PPG UNJ participants for the 2024/2025 academic year. Using a total sampling method, 100 respondents were obtained, consisting of men and women aged 23–35 years. Results: The average VO₂Max of PPG UNJ participants was approximately 38.5 ml/kg/min, which is considered moderate. Most participants had an ideal body mass index (65%). Conclusion: PPG UNJ participants had a balanced nutritional status (65%). Implications and Recommendation: a sustainable physical fitness development program is needed for PPG participants, with regular sports activities and nutrition education. The PPG UNJ participants need to gain an understanding of nutritional science material and be provided with an exercise program to stay fit and healthy.